Structure, electric, and dielectric properties of (Sr0.7Ca0.3)1.02(Zr0.95−xTi0.05Mnx)O3+δ ceramics for BME-MLCCs application - Qingyang Pang; Ying Chen; Zhixiang Wang; Bin Zhou; Xin Li; Chao Mu; Guangping Gu; Genshui Wang (Journal of Advanced Ceramics)
Zirconate-based dielectric ceramics are potential materials for base metal electrode multilayer ceramic capacitors (BME-MLCCs) due to their exceptional chemical and thermal stability, as well as excellent dielectric properties. In this work, (Sr0.7Ca0.3)1.02(Zr0.95−xTi0.05Mnx)O3+δ (SCZTM, 0 ≤ x ≤ 0.05) ceramics with two coexisting phases were prepared using a solid-state reaction method in a reducing atmosphere. This study investigates the impact of Mn doping on sintering temperature, microstructure, and electrical properties of SCZTM ceramics. Mn doping can reduce the sintering temperature from 1450 to 1300 °C. The impact of Mn doping on the structure and phonon vibration is minimal, resulting in a negligible effect on the intrinsic loss. The valence states of Mn ions and defects were characterized by X-ray photoelectron spectroscopy (XPS) and thermally stimulated depolarization current (TSDC) analysis. The results demonstrate the significant role of Mn doping in nonintrinsic loss. Due to the decrease in the concentration of oxygen vacancies (VO⋅⋅), SCZTM (x = 0.01) ceramics exhibit attractive properties: resistivity (ρ) = 8.93×1014 Ω·cm, dielectric constant (εr) = 36.16, dielectric loss (tanδ) = 2.43×10–4, temperature dependence of dielectric constant (τε) = 15.44 ppm/°C (@−55–200 °C, 1 MHz), Q×f = 30,257 GHz (@6.12 GHz), and temperature coefficient of resonant frequency (τf) = –9.9 ppm/°C. SCZTM (x = 0.01) ceramic powders were used to successfully fabricate Ni-based multilayer ceramic capacitors (MLCCs) with a high insulation resistance of IR ≥ 39.6 TΩ, an ultralow dielectric loss of tanδ = 0.2×10–4, and a wide operating temperature range (temperature coefficient of capacitance (Tcc) = 10.88 ppm/°C, @−55–200 °C, 1 MHz). SCZTM ceramics exhibit properties that make them suitable for use as BME-MLCC materials with potential market applications.